Analisis Penurunan Kadar Glukosa Fraksi n-Heksan Buah Parijoto (Medinilla speciosa B ) secara in vitro dengan Metode Spektrofotometri UV-Vis - Vifta, Rissa; Advistasari, Yustisia Dian (Indonesian Journal of Chemical Science, 2018)
Parijoto fruit (Medinilla speciosa B.) contains flavonoid compounds which are proven had activities as antiradicals and antidiabetic. The aim of this research is to know the activity of glucose level reduction in the n-hexane fraction of Parijoto Fruit (Medinilla speciosa B.). Antidiabetic activity was carried out in vitro with Nelson Somogyi reagent using UV-Vis Spectrophotometry method. The concentrations of n-hexane fractions used were 60, 80, 100, 120, 140, and 160 ppm. The test results showed that the n-hexane fraction had an activity to lower blood glucose levels with an optimum concentration of 140 ppm with percentage reduction in levels of 56.41%. Flavonoid compounds contained in the n-hexane fraction proved to have antidiabetic activity.